2021
DOI: 10.2807/1560-7917.es.2021.26.14.2001506
|View full text |Cite
|
Sign up to set email alerts
|

Determining the communicable period of SARS-CoV-2: A rapid review of the literature, March to September 2020

Abstract: Introduction Standard testing for infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is based on RT-PCR tests, but detection of viral genetic material alone does not indicate ongoing infectious potential. The ability to isolate whole virus represents a better proxy for infectivity. Aim The objective of this study was to gain an understanding of the current literature and compare the reported periods o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 163 publications
0
14
0
Order By: Relevance
“…During the first wave in spring 2020, hospitalization rates were high, reaching up to 70% in France, 55% in Spain, 50% in the United Kingdom, and 20% in Germany until the end of April. 12,13…”
Section: Introductionmentioning
confidence: 99%
“…During the first wave in spring 2020, hospitalization rates were high, reaching up to 70% in France, 55% in Spain, 50% in the United Kingdom, and 20% in Germany until the end of April. 12,13…”
Section: Introductionmentioning
confidence: 99%
“…For all variants, we are unaware of any studies which directly estimate the post-infectiousness onset recovery day distribution f r ( x ). However, viral culturing studies have consistently found live viral isolation to cease between 9 and 10 days post-symptom onset (30, 31, 41). We therefore assume a gamma distribution for f r ( x ) with mean ⟨ f r ⟩ = ⟨ f I ⟩ + 9.5 days for each variant, and we assume a scale parameter of 0.25 days to give tight distributions with relatively small interquartile ranges as indicted in (41).…”
Section: Methodsmentioning
confidence: 99%
“…Meanings of quantities are as described in Table 2. (30,31,38,41). Meanings of quantities are as described in Table 2…”
mentioning
confidence: 99%
“…For instance, if we investigate on the municipality-level, then D contains an index for each municipality. Furthermore, the values for the average latent and infectious periods ν and ω are chosen based on the literature as 3 days [25,26] and 9 days [27][28][29], respectively.…”
Section: Parameter Initialization and Data Sourcesmentioning
confidence: 99%